An empirical study of the relation between real effective exchange rate, export and economic growth in Vietnam - Van Hung Dao (Статистика и экономика, 2017)
The article focuses on qualitative and quantitative analysis of the relation between real effective exchange rate, export and economicgrowth in Vietnam. The qualitative analysis results showed that economic growth, real effective exchange rate and export in Vietnam tend to fl uctuate in the same direction. Besides, the estimation result of VECM indicated that economic growth promoted export growth through higher productivity and competitive advantages of products and real exchange rate. Thus, economic growth had a positive impact on export in Vietnam.